Sociotechnocracy in Job Training Governance: A Reflection on E-Government Practices at UPTD BLKIP Bali - Pradnyani, I Gusti Ayu Agung Dian Reditya; Prabawati, Ni Putu Anik (Baileo: Jurnal Sosial Humaniora, 2025)
This article examines the application of sociotechnocracy principles in the governance of vocational training at the Regional Technical Implementation Unit for Industrial and Tourism Training (UPTD BLKIP) in Bali Province, focusing on a critical reflection of its e-government practices. Using a qualitative descriptive approach and a case study method, the study analyzes the planning, implementation, and evaluation strategies of training programs conducted by UPTD BLKIP. The findings reveal that the strategies align with the institution’s strategic plans, including the digital simplification of registration processes, online-based promotions, and the provision of industry-relevant training. Evaluation is carried out systematically through satisfaction surveys and graduate tracking. However, the utilization of digital platforms such as SIAPkerja remains suboptimal, limiting program outreach and effectiveness. The novelty of this study lies in integrating the sociotechnocracy framework as an evaluative lens for assessing digital-based training governance in the public sector. This article recommends strengthening adaptive and data-driven digital strategies to foster more responsive and sustainable vocational training governance. The findings contribute to the development of social sciences and humanities, particularly in public policy studies, digital government, and human capital development through e-government-based training.